Pengaruh Intervensi Terapi Musik terhadap Tingkat Kecemasan pada Pasien Stroke - Murtini, Sri; Agung, Rizki Nugraha; Yunitri, Ninik; Sofiani, Yani; Silistyorini, Cahyo Ismawati (Universitas Malahayati, 2024)
ABSTRACT Stroke often leads to psychological impacts, including high levels of anxiety in patients. Uncontrolled anxiety can worsen health and hinder recovery. Music therapy, a non-pharmacological intervention, has been proven effective in reducing anxiety in stroke patients. Untreated post-stroke anxiety can affect long-term treatment processes. Music therapy uses music to achieve psychological effects on individuals. Implementing evidence-based nursing practice (EBNP) involves developing standard operating procedures (SOPs) to reduce anxiety in stroke patients through music therapy. The data analysis method used was RM ANOVA. Pre-tests and post-tests were conducted on all respondents, and then the results were compared. The number of respondents involved in the music therapy implementation was 20 respondents plus 10% for dropout risk, making a total of 22 stroke patients at the National Brain Center Prof. Dr. Mahar Mardjono East Jakarta. The EBNP implementation was carried out for 20 days, with instrumental music therapy being listened to once a day for two weeks, with a duration of 30 minutes. The health workers involved were seventh-floor nurses who were responsible for patient data collection in the E-Record Medical Records of RS PON, for patients who met the inclusion and exclusion criteria that had been determined beforehand. Music therapy significantly reduces anxiety levels (p-Value <0.001) in stroke patients with a large effect (Cohen’s d = 0.86). Posthoc analysis using the Tukey method showed a significant difference in anxiety levels in stroke patients between baseline measurements, mid-intervention, and immediate post-treatment (p-Value <0.001). The highest average change occurred between baseline measurements and immediate post-treatment (MD 7.35; p-Value <0.001). Keywords: Stroke, Music Therapy, Anxiety ABSTRAK Stroke seringkali menyebabkan dampak psikologis, termasuk kecemasan yang tinggi pada pasien. Kecemasan yang tidak terkontrol dapat memperburuk kesehatan dan menghambat pemulihan. Terapi musik, intervensi non-farmakologis, telah terbukti efektif mengurangi kecemasan pada pasien stroke. Kecemasan pasca stroke yang tidak diatasi dapat mempengaruhi proses pengobatan jangka panjang. Terapi musik digunakan untuk mencapai pengobatan efek-efek psikologis pada individu. Melakukan perawatan berbasis bukti (EBNP) melibatkan pembuatan standar prosedur operasional (SPO) untuk mengurangi kecemasan pada pasien stroke melalui terapi musik. Metode analisis data yang digunakan adalah RM ANOVA. Pre test dan post test dilakukan pada seluruh responden, kemudian hasilnya dibandingkan. Jumlah responden yang terlibat dalam penerapan terapi musik adalah 20 responden ditambah 10% untuk risiko dropout, sehingga total 22 pasien Stroke di RS Pusat Otak Nasional Prof. Dr. Mahar Mardjono Jakarta Timur. Penerapan EBNP dilakukan selama 20 hari, dengan mendengarkan musik instrumental yang diberikan sekali sehari selama dua minggu, dengan durasi 30 menit. Tenaga kesehatan yang terlibat adalah perawat lantai tujuh yang berperan dalam pendataan pasien di E-Rekam Medik RS PON, untuk pasien yang sesuai dengan kriteria inklusi dan eksklusi yang telah ditetapkan sebelumnya. Terapi musik secara signifikan mengurangi tingkat kecemasan (p-Value <0,001) pada pasien stroke dengan efek yang besar (Cohen’s d = 0,86). Analisis posthoc menggunakan metode Tukey menunjukkan perbedaan yang signifikan dalam tingkat kecemasan pada pasien stroke antara pengukuran baseline, mid intervention, dan immediate post-treatment (p-Value <0,001). Perubahan rata-rata tertinggi terjadi antara pengukuran baseline dan immediate post-treatment (MD 7,35; p-Value <0,001). Kata Kunci: Stroke, Terapi Musik, Kecemasan